Exploring the financial consequences of biodiversity disclosure: how does biodiversity disclosure affect firms' financial performance? - Raghda Abdellatif Abdelkhalik Elsayed (Future Business Journal)
Abstract This study aims to contribute to the existing business strategy and the environment literature by exploring how biodiversity disclosure affects the financial performance of firms. The study employs the content analysis of a sample of 100 Fortune Global companies for 3 years, after developing a comprehensive index to measure the quality of disclosure. Then normality, correlation, and multiple linear regression model and its estimation using ordinary least squares are performed to measure the impact of biodiversity disclosure on the financial performance of companies. In addition, the Hausman test is used to check the robustness of the study. The study results reveal a relationship between biodiversity disclosure and financial performance measured by return on assets and a stock’s price-to-book ratio. Biodiversity disclosure has a positive relationship with return on assets at a significance level below 5%. While biodiversity disclosure has a positive relationship with stock price/ book value per share, they are not statistically significant at a significance level of 5%. The sample represents only a small proportion of a larger population. The study only investigated Global 100 firms with different sectors and countries for 3 years. This study provides an opportunity to learn about the effect of the disclosure of practices associated with managing biodiversity and extinction risks through preparing a quality index of biodiversity and extinction disclosure and examining the relationship between biodiversity disclosure and the financial performance of firms by the prepared index. This study can be considered a contribution to the flow of accounting research about biodiversity and extinction. A few studies examine the effect of biodiversity disclosure. The study is among the first to examine how biodiversity disclosure affects the financial performance of firms. The results of this study inform firms and the academic literature about the economic consequences of biodiversity disclosure where biodiversity disclosure has a positive effect on firms' financial performance. The study evidence appears to be robust there is no endogeneity problem.